Alcohol Hangover Has Detrimental Impact Upon Both Executive Function and Prospective Memory - Heffernan, Thomas; Samuels, Abby; Hamilton, Colin; McGrath-Brookes, Michael (Frontiers in Psychiatry, 2019)
The alcohol-hangover (AH) is a state of general malaise following an evening of heavy episodic drinking when the blood alcohol concentration of the person reaches/approaches zero. The aim of the current study was to investigate what impact the AH has upon both executive function (EF) and prospective memory (PM). Previous research has shown that the AH has a detrimental effect upon cognitive abilities, including attention, working memory and prospective memory. The current study focused upon what impact AH might have upon both EF and related PM in the same cohort, both of which underpin everyday remembering. The current study compared an alcohol-hangover group (AHG) with a non-hangover group (NHG) on both EF and PM measures. Forty-one participants aged 18-29-years were tested; 19 comprised the Alcohol Hangover Group (AHG) and 22 of whom made up the NHG (individuals who reported no heavy drinking the day before and did not report any significant hangover symptoms). A Verbal Fluency task measured EF and the Prospective Remembering Video Procedure measured PM. The Acute Hangover Rating Scale measured alcohol-hangover symptoms and severity and a Digital Breath Analyzer Test measured their BAC. A Recreational Drug Use Questionnaire measured alcohol and other drug use. Anyone reporting having used an illicit substance across their lifetime (e.g., cannabis, ecstasy) or who smoked heavily were omitted from the study. Two univariate analyses of covariance compared the AHG and NHG groups on Verbal Fluency and Prospective Remembering Video Task scores (controlling for age, total alcohol units consumed per week and the number of years spent drinking). The AHG recalled significantly fewer items on the Verbal Fluency task [F(1, 36) = 7.42, p < 0.01] and on the Prospective Remembering Video Task NHG [F(1, 36) = 14.9, p < 0.001] when compared with the NHG. Overall, it appeared that a state of AH significantly impaired both EF and PM. Given the importance of EF and PM to everyday remembering, these findings may have farther-reaching implications.